Leveraging human centered design to enhance clinician communication during pregnancy care: Overcoming language barriers with Spanish-speaking patients - Molina, Rose L.; Bellegarde, Kasey; Long, Meghan; Bazan, Maria; Moyal-Smith, Rachel; Karlage, Ami; Schoenherr, Karen; Spigel, Lauren; DiMeo, Amanda; Herencia, Yessamin Pazos; Chakraborty, Saugata; Guise, Jeanne-Marie; et al. (PEC innovation, 2025)
Engaging patients in quality improvement and innovation projects is increasingly important, yet challenges persist with involving patients who speak languages other than English. This article presents design activities our team used to engage Spanish-speaking patients and cultural brokers. To develop a clinician communication tool to enhance patient trust in pregnancy care clinicians, especially among minoritized populations who face language and cultural barriers, using human-centered design (HCD). We centered end-user experiences, including clinicians, Spanish-speaking patients, and Spanish-speaking cultural brokers, in our design process through multiple feedback sessions and modalities. We used a HCD process to understand the problem, co-design a tool, and prepare for testing of a clinician tool. Design activities included a critical literature review, user interviews, design principles, solution sketching, rapid cycle feedback with subject matter experts, and field experience with pregnancy clinicians. We innovated on a widely used clinical communication tool, the Four Habits Model, and developed the Five Habits for Pregnancy Care to support pregnancy care clinicians in building trust by bridging cultural and language differences. We added an equity-focused habit “Pause and Reflect” to bookend the Four Habits. We refined the tool to meet different needs across pregnancy care visits based on feedback from 7 clinicians. We applied equity principles in a HCD process to understand a problem, co-design a tool, and prepare for testing by engaging with patients and cultural brokers in Spanish. Balancing the differing approaches for designers and researchers yielded important insights for enhancing equitable processes and outcomes in healthcare improvement. Communication tools designed with and for minoritized populations are critical for improving trust in all patient-clinician dyads during pregnancy care. •We used human-centered design to develop a communication tool for clinicians.•We focused on a marginalized population and engaged Spanish-speaking patients.•Enhancing communication across language barriers is critical for building trust.•The innovation includes person-centered guidance for different pregnancy visits.